Jalan Tuanku Abdul Rahman as a pedestrian street / Mazlani Sham Noor Khan - Noor Khan, Mazlani Sham (Faculty of Architecture, Planning and Surveying, 1989)
Problem associated with pedestrians are mostly linked with uncomfortability, crowding, lack of seating places, less shaded area, crossing streets, noise and air pollution, chaos and dispair while walking down a road. The reason for this research comes from the awareness for the needs of the pedestrians and as a first step towards better understanding people, the urban space and concept, the street and transportation and how they related to each other. proposing a pedestrian street is one of the solutions to overcome the problems of the pedestrians. Pedestrian street is new to Malaysian public, yet, at a glance, there a some streets that a closed for specific periods to allow for night bazaars.